(untitled) (Journal of Comparative Social Work, 2021)
One of the most frequently voiced concerns in the wake of the COVID-19 pandemic is ‘not to forget the vulnerable groups in society’. Social workers occupy a privileged position with a view to mapping such vulnerabilities, their complex interrelations, and the processes that increase the risk of falling victim to them. Therefore, in order for policy interventions aimed at mitigating negative impact on vulnerable groups to be effective, it is important to gain an in-depth insight into the first hand experiences and concomitant concerns of social workers. The main aim of this article is to describe and categorize the main concerns social workers had about their clients a few weeks into Belgium’s first wave of the pandemic. The data used derive from a large scale online survey taken among social workers in Flanders and the Brussels region in April/May 2020, closely following the lockdown on 18 March. Thematic coding analysis was used to analyse textual answers with regard to concerns about current clients. Concerns fall into six main categories, the most important one being direct concerns about the safety and wellbeing of clients in the context of various life domains (physical and mental health, family, work, education, social networks, housing, financial and material wealth), apart from concerns about communication issues more in general, about changes in the interactional dynamics between social worker and client, the effects of lockdown related changes to forms of social help, about very specific vulnerable groups, and, lastly, about the resilience of the social work sector. Analysis of the connections between concerns also enables us to reconstruct several chains of events that may result in specific (reinforced) vulnerabilities. If policy interventions aim to be attentive to such vulnerabilities, taking stock of these chains of events is of paramount importance.